Efficacy of different fungicides and Trichoderma spp. against stem rot of groundnut incited by Sclerotium rolfsii Sacc.: Efficacy of different fungicides and Trichoderma spp. against stem rot of groundnut incited by Sclerotium rolfsii Sacc. - K VINOD KUMAR; R D PRASAD; S K TRIPATHI (Journal of Oilseeds Research, 2020)
Stem rot caused by Sclerotium rolfsii Sacc. Isone of the major diseases of groundnut causing serious crop losses.Six fungicides and sixteen Trichoderma isolates were screened in vitro against Sclerotium rolfsii. Among fungicides, carboxin 37.5 % + thiram 37.5 %, tebuconazole 2% DS and mancozeb75% WP were effective in inhibiting the growth of the pathogen. Trichoderma isolates viz., T16, Th and Th11 were able to significantly inhibit mycelial growth of S. rolfsii.